Skötsel och avverkning i tätortsnära skog i Båstads kommun - Ifverson, Johan (SLU/School for Forest Management, 2016)
This work has been done together with Båstad community. It has resulted in a good planed thinning and an idea of what would be interesting for the citizens in the community. To start this work a contact was taken with the forester in Båstad Kommun to get their impact on how they were thinking about the future of the area. It was also important to get a picture of how people think a good urban forest should look like. To get this information a study was needed on what was written in this subject and what was important to think about when planning the thinning of this area.